PENERAPAN MODEL QUANTUM TEACHING DAN METODE SNOWBALL THROWING MELALUI KOLABORASI TERHADAP MINAT DAN PRESTASI BELAJAR KIMIA (Pokok Bahasan: Tata Nama Senyawa Serta Persamaan Reaksinya Pada Siswa Kelas X SMA Negeri 4 Jayapura) - MUNAWWARAH MANRUDDA; TIURLINA SIREGAR (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
This study aims toanalyze theapplication ofquantumteachinglearning modelsand methods ofsnowballthrowingthrough the collaborationof thechemicalof interest andachievement(subject: compoundnomenclatureandequationin class XSMAN 4Jayapura). The method usedin this study wasquasiexperimental witha sample of 100peopleweredivided intotwoclasses (class control and experimentalclasses). The resultsrevealthat there are differentinterests andstudent achievementbetween theclasses that usequantummodel of learningandteachingthroughcollaborationthrowingsnowballmethodused class ofmodelsthanconventional learning, evidencedthroughAsympvalue. Sig. (2-tailed) of 0.000resultingfrom theMannWhitneyUtestIn additionthere is a differenceof understandingthe concept ofstudentsas evidencedfromthe averagenormalizedgainoverallgradeof0.80compared toclassroomexperimentsusingconventional learningmodelsof 0.35. Keywords: QuantumTeaching,SnowballThrowing, InterestsLearning andLearning Achievement